2010
DOI: 10.1111/j.1464-410x.2010.09589.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management after active surveillance for low‐risk prostate cancer: pathological outcomes compared with men undergoing immediate treatment

Abstract: Study Type – Therapy (case control)
Level of Evidence 3b What's known on the subject? and What does the study add? The risks of delayed radical prostatectomy for men who progress on active surveillance are largely unknown. Two series have reported that prostatectomy after active surveillance has similar results to immediate therapy. Our data add to this growing body of evidence that appropriately selected men with prostate cancer can undergo active surveillance with delayed prostatectomy without added risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 23 publications
1
52
0
Order By: Relevance
“…Eight non-comparative studies of low-risk patients undergoing active surveillance reported prostate cancer survival rates of 100% [5][6][7][8][9][10][11][12] and another two non-comparative studies reported high prostate cancer survival rates of 97% 13 98%, respectively. 14 Studies comparing immediate RP with delayed RP in patients undergoing AS detected no significant differences in biochemical recurrence rate, positive surgical margins, extraprostatic extension, [15][16][17] and risk of incurable cancer. [18][19] Clinical outcomes following immediate or delayed surgical treatment did not differ, suggesting that there is acceptably low risk associated with undergoing AS and delaying definitive therapy.…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight non-comparative studies of low-risk patients undergoing active surveillance reported prostate cancer survival rates of 100% [5][6][7][8][9][10][11][12] and another two non-comparative studies reported high prostate cancer survival rates of 97% 13 98%, respectively. 14 Studies comparing immediate RP with delayed RP in patients undergoing AS detected no significant differences in biochemical recurrence rate, positive surgical margins, extraprostatic extension, [15][16][17] and risk of incurable cancer. [18][19] Clinical outcomes following immediate or delayed surgical treatment did not differ, suggesting that there is acceptably low risk associated with undergoing AS and delaying definitive therapy.…”
Section: Recommendationmentioning
confidence: 99%
“…Six studies conducted PSA testing every 3 months, 5,8,[14][15][16][17] 3 studies conducted PSA tests every 3 months for 1 year, 6,9,28 and 8 studies conducted PSA tests every 3 months for 2 years. 11,13,19,20,[29][30][31][32] For studies following patients beyond 2 years, PSA testing was conducted every 6 months after the second year.…”
Section: Recommendationmentioning
confidence: 99%
“…Several papers have described the outcomes from delayed intervention after a period of AS [48][49][50]. In one of the earliest reports from Johns Hopkins, rates of ''noncurable'' PCa after delayed intervention were low (23%) and did not differ from men undergoing immediate surgery [50].…”
Section: 7mentioning
confidence: 99%
“…Studies on cohorts of patients with clinically localized and non-treated prostate cancer have shown that overall survival is excellent in patients with a Gleason score of less than 7. According to Dall'Era, there is no significant prognostic difference between the low-risk patients immediately treated and those who benefited from active surveillance before surgery [28].…”
Section: Discussionmentioning
confidence: 99%